The Effect Of E-Service Quality on Purchase Decisions with Consumer Trust as a Mediating Variable - Aini, Safira Nur; Juliati, Ratih; Putri, Viajeng Purnama (Universitas Muhammadiyah Malang, 2024)
This research was conducted on Grosir Asemka consumers who made purchases through the Shopee marketplace, with the aim of the study to determine: the effect of e-service quality on purchasing decisions, es-service quality on consumer trust, consumer trust in purchasing decisions and e-service quality on purchasing decisions through consumer trust. This research uses the SPSS 25 for Windows Program tool, and uses 125 respondents. The results of this study are as follows: e-service quality has a positive and significant effect on purchasing decisions, e-service quality has a positive and significant effect on consumer trust, consumer trust has a positive and significant effect on purchasing decisions, and consumer trust has a mediating role in the relationship between e-service quality and purchasing decisions.